Global research trends and frontiers in patent foramen ovale closure: a comprehensive bibliometric analysis (2004–2024) - Liu, Jie; Liu, Yehong; Sheng, Ying; Ye, Jiangping; Yuan, Rikang; Wang, Xiao; Zong, Gangjun (Frontiers in Neurology, 2025)
BackgroundPatent foramen ovale (PFO), present in 20–30% of the population, was once considered benign but is now recognized as a contributor to cryptogenic stroke and other clinical syndromes. Recent randomized trials and updated guidelines have established PFO closure as an effective intervention, leading to a surge in research. This study uses bibliometric analysis to evaluate global research trends, collaborations, and emerging hotspots in PFO closure.MethodsWe analyzed 927 English-language articles (2004–2024) from the Web of Science Core Collection using bibliometric tools (VOSviewer, CiteSpace, Bibliometrix R, online bibliometric analysis platforms). We systematically examined publication trends, contributions by countries and institutions, author networks, journal influence, and keyword clusters.ResultsAnnual publications increased significantly after 2017, coinciding with pivotal trial results. The United States (34.6%), Italy (16.8%), and Germany (11.5%) led in research output. Key institutions (e.g., University of Bern) and prominent authors (e.g., Meier Bernhard) played central roles. Four major research clusters were identified: mechanisms of paradoxical embolism, diagnostic imaging (e.g., transesophageal echocardiography), closure techniques (e.g., Amplatzer devices), and clinical outcomes. Burst detection revealed evolving priorities, including post-closure atrial fibrillation and improved patient selection (e.g., RoPE score).ConclusionResearch on PFO closure has progressed from pathophysiological understanding to evidence-based clinical intervention, driven by landmark trials and multidisciplinary collaboration. Future directions include optimizing patient selection, managing post-procedural complications, and expanding indications (e.g., migraine). This analysis offers a roadmap for advancing stroke prevention strategies related to PFO.